The development of children's thinking its social and communicative foundations - Carpendale, Jeremy I. M. 1957-; Lewis, Charlie; Müller, Ulrich 1964- (Los Angeles Sage, 2018)
"The Development of Children's Thinking offers undergraduate and graduate students in psychology and other disciplines an introduction to several core areas of developmental psychology. It examines recent empirical research within the context of longstanding theoretical debates. In particular, it shows how a grasp of classic theories within developmental psychology is vital for a grasp of new areas of research such as cognitive neuroscience that have impacted on our understanding of how children develop"--Provided by publisher.
Chapter 1: Introduction: What is Human Thinking and How Does it Develop? -- Chapter 2: The Role of Biology in Psychological Development -- Chapter 3: Constructivist Approaches to Children's Thinking -- Chapter 4: Sociocultural Approaches to Children's Thinking -- Chapter 5: The Development of Communication and Social Understanding in Infancy -- Chapter 6: Theories of Communication and Social Understanding in Infancy -- Chapter 7: Animal Communication and Human Language -- Chapter 8: Language in Human Communication and Thinking -- Chapter 9: How Children Learn the Meaning of Words -- Chapter 10: How Children Come to Control Their Behaviour -- Chapter 11: Understanding the Social World -- Chapter 12: Social Interaction, Language and Social Understanding -- Chapter 13: Moral Reasoning and Action -- Chapter 14: Recent Issues in Moral Development.
Keywords: Child development